Mosaic loss of chromosome Y in blood is associated with male susceptibility for idiopathic pulmonary fibrosis - Josefin Bjurling; Nicholas W. Chavkin; Jonatan Halvardson; Mark C. Thel; Jonas Mattisson; John S. Kim; Ammar Zaghlool; Shwu-Fan Ma; Fernando J. Martinez; Kevin Anstrom; Imre Noth; Kenneth Walsh; et al. (Communications Medicine, 2025)
Abstract Background The prevalence of idiopathic pulmonary fibrosis (IPF) is higher in men, a previously not well-understood sex bias that extends across severity and mortality. Mosaic loss of chromosome Y (mLOY) in blood is male-specific and associated with adverse outcomes, including IPF. In mLOY-mice, enhanced TGF-β signaling has been reported to contribute to fibrosis of internal organs, but it is not known if such mLOY-driven disease mechanism exists in humans. Methods We focused here on IPF in men to investigate if mLOY contributes to fibrotic disease processes in humans, as demonstrated in mouse models. To this end, we investigated mLOY as a risk factor for male IPF in epidemiological and clinical datasets, as well as by re-analyses of published single-cell RNA sequencing (scRNAseq) datasets. Results We find that men with mLOY in blood display an increased risk for IPF diagnosis and death caused by IPF in UK Biobank, and that mLOY is associated with reduced lung functions in two cohorts. Approximately 80% of the male excess in IPF prevalence occurs in the group of men with mLOY in blood leukocytes. Notably, scRNAseq analyses support that pulmonary leukocytes with Y loss exacerbate IPF by upregulating profibrotic genes and enhancing TGF-β signaling. Conclusions Our results contribute to explaining the profound sex bias in IPF and replicate a mLOY-driven profibrotic disease mechanism first identified in mice. Male IPF patients with mLOY represent a subgroup that may benefit from treatment with TGF-β inhibitors.